She Costume in Southeastern China: Ethnic identity, bodily practices and local fashion styles in the process of globalisation - Tu, Shaorong; Phanlukthao, Peera (Edelweiss Applied Science and Technology, 2025)
This study examines She Costume and its culture in southeastern China, focusing on the 'phoenix costume'. The four objectives of the study are (1) historical and structural analysis of She Costume; (2) the impact of globalisation on ethnic identity; (3) evolving bodily practices; (4) integration into contemporary fashion as a 'local fashion style'. A qualitative methodology was used, combining fieldwork and archival research (historical texts, genealogy) with case studies of cultural innovations. The findings show that She Costume has developed a variety of different styles due to its migratory history. Analysing the text in terms of five different styles, it is found that the phoenix costume, characterised by symbolic motifs (e.g., the phoenix totem) and craftsmanship, is a typical feature of the She Costume. Globalisation has driven the modernisation of designs and materials, facilitated the development of hybrid styles, but also posed the risk of the erosion of traditional skills. The study concluded that She Costume strikes a balance between traditional She Costume and modernity through adaptive innovation.